Treatment of class II, division 2 malocclusion with external root resorption due to dentoalveolar trauma. A case report - Campuzano, Adriana; Botero, Paola María (Revista Facultad de Odontología Universidad de Antioquia, 2014)
The literature reports that patients who have suffered dentoalveolar trauma, and therefore have experienced external root resorption, are at higher risk of reactivating the resorption process after applying orthodontic forces. This risk increases with uncontrolled tooth movements, intrusion movements, extended orthodontic treatment, and application of extreme forces, among other factors. Intrusion movements are considered the riskiest for root resorption, although it has been shown that they are directly proportional to the magnitude of applied forces. This case report refers to a 13-year-old patient with history of external root resorption due to trauma at the age of 7. Despite the intrusion movement (Ricketts intrusion arch) of the affected teeth, the clinicians were able to maintain the initial root length of resorpted teeth. Besides proper management of movement and forces, an excellent radiographic control was performed quarterly, as well as regular consultation with an endodontist.